Corticosteroids and the Pharmacological Management of Autism—An Integrative Review - Lillian Amanda Gabarrão de Jesus; Grasiela Piuvezam; Isac Davidson Santiago Fernandes Pimenta; Eduardo Borges de Melo (Scientia Pharmaceutica)
Autism spectrum disorder (ASD), or autism, is a lifelong neurodevelopmental condition typically detected during early childhood, for which no specific and efficient pharmacological management is currently available. No drugs have been developed specifically for the pharmacological management of autism. Thus, this approach often relies on various conventional psychotropic medications and, depending on the condition, other medications may also be used. Some studies available in the literature indicate that the adjunctive use of corticosteroids can help improve the quality of life of individuals with autism. Therefore, we conducted an integrative review using four databases, which were PubMed, Scopus, Web of Science, and Google Scholar, focusing on clinical trials and animal model studies involving corticosteroids related to autism. We analyzed the effects of treatment on core and associated autism symptoms, as well as adverse effects. Eight studies were selected and analyzed, seven involving humans and one using an animal model. These studies focused on the drugs pregnenolone (3), prednisolone (3), hydrocortisone (1), and betamethasone (1) in trials either alone or in combination with other medications (such as risperidone). We observed that corticosteroids safely and effectively reduced several symptoms, including stereotypical and social behaviors, hyperactivity, and irritability. Furthermore, no serious adverse effects were observed, although all selected studies were of short duration. Thus, corticosteroids are promising options to be included in the pharmacological management of autism, whether or not in combination with other medications, and further studies are needed to evaluate their long-term effectiveness.